The Implementation and Impact of Gender Mainstreaming in Saudi Arabia in 2016-2022 - Aini, Shenndy Fadilah Nurul; Wiranata, I Made Anom; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
This research explains the implementation and impact of gender mainstreaming in Saudi Arabia in 2016-2022 after the birth of the Saudi Arabian Vision 2030. This paper uses the concept of gender mainstreaming and norm diffusion theory. The concept of gender mainstreaming is used to see the implementation of gender mainstreaming through gender responsive policies to overcome the gender gap in Saudi Arabia and through this implementation the results will be seen in various fields such as economics, social culture and politics. Norm diffusion as a supporting theory that strengthens the concept of gender mainstreaming in explaining the implementation and impact of gender mainstreaming in Saudi Arabia. The results obtained are that gender mainstreaming has positive and negative impacts in various fields.    Keywords : Gender Mainstreaming, Saudi Arabia, Saudi Vision 2030